1971
DOI: 10.1002/bit.260130507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of additives on mass transfer in turbine aeration

Abstract: SummaryMass transfer coefficients and interfacial areas were determined for the aeration of aqueous solutions in a turbine agitated vessel. The mass transfer coefficients measured for water without additive and for sodium chloride solutions matched very well to measurements in the literature for air bubbles of the same diameter in free rise. Thus the only effect of agitation was to determine the bubble size which then in turn set the coefficient. Two surface active agents were studied: sodium dodecyl sulfate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…every 15 minutes. The oxygen mass transfer coefficient k L a of the bioreactor was taken into account and measured as described by the procedure proposed by Benedek and Heideger [13] and adapted by Sheppard [14]. All aerobic experiments were conducted at room temperature (22°C).…”
Section: Methodsmentioning
confidence: 99%
“…every 15 minutes. The oxygen mass transfer coefficient k L a of the bioreactor was taken into account and measured as described by the procedure proposed by Benedek and Heideger [13] and adapted by Sheppard [14]. All aerobic experiments were conducted at room temperature (22°C).…”
Section: Methodsmentioning
confidence: 99%
“…Sheppard and Cooper (1990) suggest that the diffusional resistance effect will dominate at low surfactant concentrations (therefore, KLa will decrease), while at high surfactant concentrations the interfacial area effect will predominate (therefore, KLa will increase). Results obtained by Benedek and Heideger (1971) indicate that the agitation rate does not affirect ....... ~L ; thus, the effect of agitation on KLa is through its effect on the interfacial area. If this is true, then the results obtained at 0.07 vvm indicate that the effect of agitation on theinterfacial area is reduced when Pluronic F-68 is present.…”
Section: Resultsmentioning
confidence: 88%
“…Lavery and Nienow found that used TNM-FH insect cell culture medium agitated by a single rnarine impeller of 4 cm diameter. Benedek and Heideger (1971) found that adding antifoam to water inhibited KLa less at 255 rpm than at higher agitation rates when sparged at 0.39 vvm. All of these results demonstrate that at a low sparge rate the addition of either antifoam or Pluronic F-68 results in an increased inhibition of KLa as the agitation rate is increased.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, the presence of surfactants can reduce k L by reducing turbulence on a microscopic scale in the interfacial region. Therefore, the net effect of electrolytes and surfactants can be an increase or a decrease in kia [78].…”
Section: The Effect Of Solution Compositionmentioning
confidence: 99%